Diet, Obesity, and Reactive Oxygen Species – Implications for Diabetes and Aging - Newsholme, Philip; Krause, M. (Springer Verlag, 2014)
An increase in reactive oxygen species (ROS) and a decrease in endogenous antioxidant defense mechanisms are observed in both aging and diabetes. The mechanisms driving an increase in ROS are generally associated with low-grade inflammation in obesity, diabetes and aging. The sources of ROS, sources of antioxidants, and the impact on mitochondrial function are described in this chapter and the relevance of imbalances in favor of ROS generation to loss of muscle function in both aging and diabetes are described in more detail.